PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS PROBLEM BASED LEARNING DAN JUMPING TASK PADA POKOK BAHASAN KAIDAH PENCACAHAN UNTUK SISWA SMA - Rizqika, Putri; Hobri, H; Murtikusuma, Randi Pratama (Department of Mathematics Education , University of Jember, 2019)
This research aims to (1) describe the process of developing learning instrument based on problem based learning model and jumping task based on enumeration rule for high school students; (2) describe the of developing learning instrument based on problem based learning model and jumping task based on enumeration rule for high school students. The learning instrument developed are Lesson Plan and Student’s Worksheets. This research took place at XI MIPA 5 of senior high school 1 Tempeh, Lumajang with consists 33 students. This research is development research. Steps and results from development were (1) the development process of using modified Thiagarajan, Semmel, and modified Semmel model which consists of 3 stages, (2) development results were validation test from validation sheet analysis that score 3.54 for Lesson Plan validatiy coefficient and 3,54 for Student work sheets validaty coefficient with valid category, practicality test from teacher’s activity analysis scored 88,88% for the first meeting and 93,05% for the second meeting with good category and include in practical category, and efectiveness test from students activity analysis in the first and second meeting that the average percentage was 92.05% and 93.18%, average of student’s questionnaire results obtained 90,90%, and the average Learning Result Test results obtained 78.19 and the percentage of Learning Result Test is 78.78% in the effective category. Keyword : Learning Instrumen, Problem Based Learning, Jumping Task, Enumeration Rule